Microscopic Rocks and Expansive Empires: Investigating Inca Ceramics from Cuzco, Peru. Issue 1 (23rd October 2014) - Ixer, Rob; Lunt, Sara; Sillar, Bill; Thompson, Patrick
Abstract : High quality polychrome ceramics are an iconic aspect of Inca material culture. This 'Cuzco Inca' pottery appears suddenly in the archaeological record: but it draws upon technological and stylistic aspects of earlier local pottery and we discuss the specifics of how these pre-Inca traits were combined to form the distinctive new state ceramics. Using ceramic petrography, the dominant fabric of Cuzco Inca pottery is compared with those of two pre-Inca wares, Killke and Lucre. Andesite temper, identified in the Lucre and Cuzco Inca fabrics, is compared with samples of andesite from local geological outcrops. This suggests that Lucre pottery was made using similar materials to Cuzco Inca and was a technological precursor. Because these materials and technological knowledge would only have become available to the Inca after their conquest of the Lucre cultural area, this ceramic evidence has important implications for our understanding of Imperial expansion and state intervention in craft-production.